Age And Sex Matched Data- Two Ears Improved Social Interaction And Quality Of Life - Okşan ERKAN, Sanem; TUHANİOĞLU, Birgül (ENT Updates, 2019)
Introduction: Hearing aids are electronic devices used by individuals with hearing loss to improve their quality of life. It is more useful to use bilateral hearing aids. Thus, the localization of the sound is better determined and an additional 6-10 dB increase in sound intensity can be achieved. In our study, we compared the satisfaction level of patients with hearing loss who used unilateral or bilateral devices. Methods: Patients with bilateral sensorineural hearing loss and using unilateral or bilateral hearing aids for at least 3 months and whose hearing loss cannot be treated with medical or surgical treatments were included. International Outcome Inventory for Hearing Aids Turkish Version (IOIHA-TR) was administered to them. Results: Matched data were used to standardize age and gender between the groups. In high school bilateral fitting increased. There was no difference between the groups in terms of hearing pure tone thresholds and speech discriminations. There was a significant difference between the groups in terms of the mean score of question 5 (p=0.047), question 7 (p=0.022) and mean total scale (p=0.028) in IOI-HA-TR. Conclusion: As a result, we found that the satisfaction level of bilateral hearing aid users was higher. Bilateral hearing aid use has a positive effect on the